TRIVIDHA KARMA IN SURGICAL PARLANCE- A CONCEPTUAL STUDY - Gupta Pooja*; Gupta Arjun; Bharti Neeru; Hiteshi (AYUSHDHARA, 2020)
In Ayurvedic classics there are various types of treatment and Shastra chikitsa is one among them. Purva Karma Pradhana Karma, Paschat Karma are Trividha Karma. According to Acharya Sushruta, Purva Karma means preparation of patient along with collecting all the materials needed during the Pradhana karma. Ashtaviddha Shastra Karma is included in Pradhana Karma. Paschat Karma includes post operative care. Sushruta division of surgical activity into three parts i.e., pre- operative, operative and post-operative based on sound scientific principles. Sushruta has also described the pre-operative appreciation of foreign body, its size, shape, and exact location within the body and appropriate instrument for its removal should be selected pre-operatively. He has also mentioned the pre-operative diet and starvation for various types of surgeries. He has also emphasized that asepsis and antisepsis precaution should be taken, wound should be protected from dangerous and invisible creatures (Nishachara). Fumigation of Vranitaagara should be done for ten days, twice a day. By virtue of this article, we can understand the systematic method of arranging the surgical experience of arranging the surgical experience of the older surgeon, about preliminary measures, principal measures and after measures. All the procedures included under these three headings i.e., Trividdha karma plays an important role in successful and complication free surgery.